2021
DOI: 10.1016/j.vaccine.2020.12.085
|View full text |Cite
|
Sign up to set email alerts
|

Advancing innovation for vaccine manufacturers from developing countries: Prioritization, barriers, opportunities

Abstract: Highlights 95% of respondents manufacturers have a strategy to pursue innovation. Innovation targeted at low- and middle- income countries. Partnerships with biotechs and universities key in driving innovation. Access to partnerships, in-licensing/ joint ventures seen as barrier to novel vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Given the high-cost and complexity of in-house development, often manufacturers engage in licensing agreements and joint ventures to access new technologies and expertise. Recent research has revealed that partnerships for novel and improved vaccines between DCVMN members is particularly low, with manufacturers electing to engage with biotechnology companies and academic institutions [19] . Our matching analysis, illustrated in Figure 3 , suggests that there are ample opportunities for ‘South-South’ collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high-cost and complexity of in-house development, often manufacturers engage in licensing agreements and joint ventures to access new technologies and expertise. Recent research has revealed that partnerships for novel and improved vaccines between DCVMN members is particularly low, with manufacturers electing to engage with biotechnology companies and academic institutions [19] . Our matching analysis, illustrated in Figure 3 , suggests that there are ample opportunities for ‘South-South’ collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…Other political, economic, and social factors are also involved. These are illustrated in Hayman et al, Kraigsley et al, and Phillips et al [113][114][115]. Lowering the overall manufacturing costs is an essential requitement to help LMICs to become more independent.…”
Section: Some Economic Considerationsmentioning
confidence: 99%
“…Other political, economic, and social factors are also involved. These are illustrated in Hayman et al, Kraigsley et al, and Phillips et al [ 113 , 114 , 115 ].…”
Section: Some Economic Considerationsmentioning
confidence: 99%
“…Moreover, most vaccine manufacturers in these countries lack high-level technical expertise, which presents further challenges for gaining access to best practices and know-how. A recent study has shown that the number of LMICs that can currently translate shared key knowledge into production capacity is still a minority [25].…”
Section: International Efforts During the Covid-19 Pandemicsmentioning
confidence: 99%